Introduction of Enhanced Recovery for Elective Cesarean Section Enabling Next Day Discharge: A Tertiary Centre Experience. Issue 2 (June 2016) - Wrench, I.J.; Allison, A.; Galimberti, A.; Radley, S.; Wilson, M.J.
Abstract : ( Int J Obstet Anesth. 2015;24(2):124–130) Enhanced recovery programs (fast-track surgery) are designed to optimize aspects of patient care after surgery in order to improve recovery and facilitate earlier discharge without reducing quality of care or patient satisfaction. There is mounting evidence linking enhanced recovery programs to improved patient outcomes postoperatively, including reduced patient morbidity, reduced length of stay, and earlier return to normal activities.